2022
DOI: 10.1108/jima-01-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan effect and indices movement estimation: a case study from eight Arab countries

Abstract: Purpose This study aims to investigate the Ramadan effect anomaly on the stock markets’ indices and estimate the movement of these indices in the light of the phenomenon. Design/methodology/approach Stock market indices are used as financial indicators to show the Ramadan effect. To validate this effect, eight Arab countries, which comprises Jordan, Saudi Arabia, Oman, Qatar, United Arab Emirates, Bahrain, Kuwait and Egypt, are adopted. A linear regression with R2, error, F-value and p-value is considered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…On the other hand, various researchers have investigated the effects of international and local events on stock markets, food security indices, and prices. Many events have been considered by these researchers, such as air quality [ 50 ], Ramadan Effects [ 51 ], Syrian Refugee Influx [ 52 ], Crop yield indices [ 5 ], and oil prices [ 53 ]. Table 1 shows several studies that discussed food security issues and several crises that occurred recently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, various researchers have investigated the effects of international and local events on stock markets, food security indices, and prices. Many events have been considered by these researchers, such as air quality [ 50 ], Ramadan Effects [ 51 ], Syrian Refugee Influx [ 52 ], Crop yield indices [ 5 ], and oil prices [ 53 ]. Table 1 shows several studies that discussed food security issues and several crises that occurred recently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, numerous researchers have directed their attention toward comprehending the influence of various events on stock market indices across different countries, employing diverse methodologies. Al-Najjar et al (2022a) estimated the stock indices in Gulf countries by considering Ramadan as studied variable. The study showed that Ramadan has a strong relationship with stock indices in some Gulf countries, and in other countries, there is no effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e dataset is divided into three datasets: train, validate, and test. e data are divided randomly with 70%, 15%, and 15% of the data for training, validating, and testing, respectively, as discussed by Al-Rousan et al [38], AL-Najjar [39], and AL-Najjar et al [40]. e training dataset is used to build a prediction model.…”
Section: Develop Prediction Models Based On Cr-tree and Chaid Modelmentioning
confidence: 99%